Modeling the Intention to Choose Natural Vaginal Delivery: Using Reasoned Action and Social Cognitive Theories - Safieh Kanani; Hamid Allahverdipour; Mohammad AsghariJafarabadi (Tabriz University of Medical Sciences, 2015)
Background: The Behavioral Intention Model is one of the best and most widely models used regarding attitude of behavioral of pregnancy and decrease the rate of cesarean section (CS) among pregnant women, except effect of atti-tude and subjective norms on behavioral intention. Two variables of self-efficacy, and outcome expectation, relate to individual's behavior in an upcoming situation, and both of them are important at the development of behavior. The purpose of the present study was to develop a model to explain women's inten-tion to choose natural vaginal delivery (NVD). The variables of self-efficacy and outcome expectations, derived from Bandura's Social Cognitive Theory, and Behavioral Intention Model constructs were used to define the model.Methods: The study was descriptive and cross-sectional in nature and took place in Pars Abad, Iran in 2014. The non-probability sample consisted of 200 pregnant women who voluntarily participated in the study and provided the data. SPSS 21 and MPLUS 6.8 were employed to analyze the data.Results: Self-efficacy, outcome expectations, and attitude toward NVD were associated with intention to choose the NVD.Conclusion: The study findings may play a role in designing educational inter-ventions aimed at influencing the NVD and improving childbirth programs.